Preparation method of erbium-doped TiO2 / diatomite composite photocatalytic material

By preparing erbium-doped nanotitanium dioxide on diatomaceous earth, expanding its spectral response range and improving dispersion, the low efficiency and safety problems of nanotitanium dioxide photocatalytic materials in the treatment of low concentrations of harmful gaseous pollutants are solved, and high efficiency is achieved , environmentally friendly air purification effect.

CN119259022APending Publication Date: 2025-01-07NANJING COLLEGE OF INFORMATION TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411405518.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing nanotitanium dioxide photocatalytic materials are inefficient in the treatment of low concentration harmful gaseous pollutants, high cost, difficult to recover, and have problems with secondary pollution and ultraviolet radiation safety.

Method used

Erbium-doped TiO2/diatomaceous earth composite photocatalytic material was prepared by sol-gel method. By attaching erbium-doped titanium dioxide particles to the surface of diatomaceous earth, the spectral response range is extended to the visible light area, and the diatomaceous earth load is improved The dispersion of nanoparticles increases the stability and utilization of materials.

Benefits of technology

It realizes efficient degradation of organic polluted gases under visible light, avoids secondary pollution and ultraviolet radiation safety issues, reduces renewal costs, and improves the flexural and compressive strength of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259022A_ABST
    Figure CN119259022A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalytic materials, and particularly relates to a preparation method of an erbium-doped TiO2 / diatomite composite photocatalytic material, which comprises the following steps: by adopting a sol-gel method, taking purified diatomite as a carrier, taking butyl titanate as a titanium source, and doping erbium to prepare diatomite-loaded erbium-doped nano TiO2 powder; the preparation method comprises the following steps: mixing diatomite loaded erbium-doped nano TiO2 powder with water, plant debris, a binder, a thickener and a dispersant to obtain an erbium-doped TiO2 / diatomite composite photocatalytic material; the preparation method of the diatomite-loaded erbium-doped nano TiO2 powder comprises the following steps: adding butyl titanate and glacial acetic acid into a diatomite suspension, then dropwise adding an erbium acetate solution, and controlling the molar ratio of Er < 3 + > to Ti < 4 + > in the diatomite-loaded erbium-doped nano TiO2 powder to be (0.5-1): 100. According to the catalytic material, the spectral response range of TiO2 is expanded to a visible light region through erbium doping, so that the material can effectively degrade and remove organic pollution gas under visible light, and secondary pollution and ultraviolet radiation safety problems are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic materials, and in particular relates to a method for preparing an erbium-doped TiO2 / diatomite composite photocatalytic material. Background Art

[0002] With the rapid economic development and the continuous improvement of people's living standards, people are more and more eager to have a healthy, safe and comfortable indoor environment. Indoor air pollutants can be classified into two categories: suspended particulate pollutants and harmful gaseous pollutants. Harmful gaseous pollutants are generally composed of organic compounds such as benzene, toluene and formaldehyde. Among them, formaldehyde has been identified by the World Health Organization as a potential strong carcinogen, which seriously endangers people's health.

[0003] Traditional low-solubility harmful gaseous pollutant purification materials are mostly natural mineral adsorbents such as activated carbon, diatomaceous earth, zeolite, and mixed adsorbents containing photocatalytic materials. Among them, natural mineral adsorbents can only adsorb and fix harmful gaseous pollutants. After a period of adsorption, they reach saturation and need to be regenerated or replaced, which increases the cost of use and is prone to secondary pollution. Mixed adsorbents containing photocatalytic materials can degrade and remove harmful gaseous pollutants, but they need to use ultraviolet light to stimulate the activity of photocatalytic materials, which has problems with ultraviolet radiation safety and low purification efficiency.

[0004] Nano-titanium dioxide (TiO2) is a commonly used photocatalytic material. It has broad application prospects in the treatment of organic pollutants in the atmosphere and aquatic environment due to its advantages such as safety and non-toxicity, high photocatalytic activity, strong oxidation ability, stable photochemical performance and low price. However, in practical applications, TiO2 has two defects: one is that it can only be excited by ultraviolet light, the utilization rate of sunlight is low, generally less than 5%, and photogenerated electrons and holes are easy to recombine; the other is that the nanoparticles have poor dispersion and are easy to agglomerate. Both of these defects will lead to low photocatalytic efficiency of TiO2. The solution to these problems is to dope and modify TiO2 and fix the load. The purpose of doping is to expand the light response range of the photocatalyst to the visible light region and inhibit the recombination of electron-hole pairs, while loading can avoid the agglomeration of nanoparticles and further enhance the photocatalytic efficiency of TiO2.

[0005] At present, the ions doped and modified by TiO2 mainly include metal ions and non-metal ions, which are usually doped in a single or co-doped manner. The light response range of TiO2 doped with different ions can be extended to the visible light region, which improves the utilization rate of sunlight. Non-metal ion doping modification will introduce oxygen vacancies in the TiO2 lattice as charge recombination centers, reducing the visible light catalytic efficiency of the photocatalyst; at the same time, during the heat treatment process, some unstable or toxic non-metal elements will evaporate in the form of vapors, causing environmental pollution and reducing the doping efficiency. Metal ion doping modification is generally divided into precious metal doping, transition metal doping and rare earth element doping. Among them, precious metal doping has a high cost, low recycling rate and short service life; transition metal doping reaction performance is not stable enough, and more stringent process conditions are required to ensure the visible light catalytic efficiency of the photocatalyst; rare earth element doping can increase the adsorption of organic pollutants by TiO2, and can also delay the transformation of anatase phase to rutile phase, thereby enhancing the photocatalytic performance of TiO2. Diatomaceous earth is a natural mineral material formed by the accumulation of diatom debris for many years. It has the advantages of small particle size, large specific surface area, high porosity, stable chemical properties, strong adsorption capacity, etc. It is an excellent photocatalyst carrier material and is widely used in the fields of chemical industry, building materials, air purification, etc. TiO2 powder is loaded on the surface of diatomaceous earth to ensure its good catalytic activity.

[0006] However, if Er-doped TiO2 / diatomite powder is directly used for air purification, there are still problems such as high cost, difficult recycling, unsafety, low utilization rate and secondary pollution. Therefore, it is necessary to find appropriate methods and reasonable technologies to solve the use problems of nano-TiO2 powder after loading and modification. Summary of the invention

[0007] In view of the deficiencies of the prior art, the present invention provides a method for preparing an erbium-doped TiO2 / diatomite composite photocatalytic material, which overcomes the deficiencies of the prior art nano-titanium dioxide photocatalytic material in the treatment technology of low-concentration harmful gaseous pollutants.

[0008] The technical solution provided by the present invention is as follows:

[0009] The present invention provides a method for preparing an erbium-doped TiO2 / diatomite composite photocatalytic material, comprising the following steps: The sol-gel method was used to prepare diatomite-loaded erbium-doped nano-TiO2 powder by doping erbium with purified diatomite as carrier and butyl titanate as titanium source. The diatomite-loaded erbium-doped nano-TiO2 powder is mixed with water, plant debris, a binder, a thickener and a dispersant to obtain an erbium-doped TiO2 / diatomite composite photocatalytic material; The preparation method of diatomite-loaded erbium-doped nano-TiO2 powder comprises: firstly adding butyl titanate and glacial acetic acid to a diatomite suspension, then dripping an erbium acetate solution, and controlling the Er content in the diatomite-loaded erbium-doped nano-TiO2 powder to increase. 3+ With Ti 4+ The molar ratio is 0.5~1:100.

[0010] Furthermore, the method of first adding butyl titanate and glacial acetic acid to the diatomite suspension and then dropwise adding the erbium acetate solution comprises: The purified diatomaceous earth and anhydrous ethanol solvent are fully stirred and mixed, and a diatomaceous earth suspension is prepared under ultrasonic treatment; butyl titanate and glacial acetic acid are sequentially added to the suspension and stirred and mixed to obtain a mixed solution; 0.1 g of erbium acetate is dissolved in 2 mL of deionized water, and then an appropriate amount of nitric acid is added to adjust the pH value to 3 to prepare an erbium acetate solution; the erbium acetate solution is added dropwise into the mixed solution and stirred to hydrolyze and condense butyl titanate in the mixed solution to produce titanium dioxide, thereby generating titanium dioxide colloid particles doped with erbium ions attached to the surface and pores of diatomite; after the hydrolysis and condensation reactions are completed, a sol is obtained; during the reaction, glacial acetic acid is added to inhibit hydrolysis; The method for preparing the diatomite-loaded erbium-doped nano-TiO2 powder also includes: Polyethylene glycol solution is added to the above sol, and the mixture is stirred to obtain a gel, which is aged, vacuum dried, ground and calcined to obtain diatomaceous earth-loaded erbium-doped nano-TiO2 powder.

[0011] Furthermore, the mass ratio of the produced titanium dioxide to diatomaceous earth is 1:1.5-2, and the volume ratio of butyl titanate to glacial acetic acid is 1:0.4-0.5.

[0012] Furthermore, the erbium acetate solution is added dropwise to the mixed solution at a rate of 1 drop every 3 to 5 seconds.

[0013] Furthermore, the mass volume ratio of polyethylene glycol to sol is 0.3-0.4:100 g / mL.

[0014] Furthermore, the aging conditions are to react at 25°C for 24 hours, the vacuum drying conditions are to dry at 80°C and an absolute pressure of 10 kPa for 8 hours and keep warm for 16 to 24 hours, and the calcination conditions are to heat to 500°C at a heating rate of 5°C / min in a muffle furnace and calcine at this temperature for 2 hours.

[0015] Furthermore, when the mixture of diatomaceous earth and anhydrous ethanol is stirred, the stirring speed is 800-1000 rpm. When the sol and gel are obtained by stirring, the stirring speed is 2000 rpm.

[0016] Furthermore, the diatomite-loaded erbium-doped nano-TiO2 powder is mixed with water, plant debris, a binder, a thickener and a dispersant, and the proportions of each substance are calculated according to the following weight parts: 25~35 parts water, 40~50 parts of diatomite-loaded erbium-doped nano-TiO2 powder, 5-10 portions of plant debris, 3~5 parts of adhesive, Thickener 2~5 parts, 3~5 parts of dispersant.

[0017] Furthermore, the binder is glutinous rice glue powder, the thickener is sodium carboxymethyl cellulose, the dispersant is carboxylic acid copolymer salts, and the plant debris is prepared by freeze-drying plant leaves at -80°C and 0.2MPa for 72 hours, grinding and crushing, and then passing through a 300-325 mesh sieve.

[0018] Further, the steps of purifying diatomite are: The diatomaceous earth is sieved with a 325-mesh sieve, and the diatomaceous earth under the sieve is placed in a 60wt% sulfuric acid aqueous solution and stirred for washing for 2-3 hours; then, it is treated with an ultrasonic wave with a power of 200-250W for 1-2 hours at 25-30°C, and then washed with distilled water until neutral; then, it is placed in a vacuum drying oven and dried at 80°C for 6 hours; finally, it is placed in a muffle furnace and calcined at 550-600°C for 3 hours to obtain purified diatomaceous earth, which is placed in a dryer for standby use.

[0019] Beneficial Effects

[0020] The composite photocatalytic material prepared by the present invention expands the spectral response range of TiO2 to the visible light region by erbium doping, so that the material can effectively degrade and remove organic pollutant gases under visible light without causing secondary pollution and ultraviolet radiation safety problems; the dispersibility of TiO2 nanoparticles can be changed by diatomaceous earth loading, so that the TiO2 nanoparticles can be evenly dispersed in the three-dimensional microporous structure of diatomaceous earth, thereby increasing the contact area between the TiO2 nanoparticles and the organic pollutant gases; the finished material is made into reusable round particles, which solves the problems of high renewal cost and difficult powder recovery; and the finished material particles can have strong flexural and compressive strengths by adding plant debris.

[0021] Through formaldehyde degradation experiments, the formaldehyde degradation removal rate of the composite photocatalytic material based on unmodified TiO2 / diatomaceous earth powder (TD) was 85.85% within 180 minutes, while the formaldehyde degradation removal rate of the composite photocatalytic material based on erbium-doped TiO2 / diatomaceous earth powder (ErTD) was 97.92% within 180 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a process flow chart for preparing diatomite-loaded erbium-doped nano-TiO2 powder.

[0023] Figure 2 This is a SEM image of diatomite-loaded erbium-doped nano-TiO2 powder of the present invention.

[0024] Figure 3 This is a schematic diagram of the formaldehyde degradation test comparison. DETAILED DESCRIPTION

[0025] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing an erbium-doped TiO2 / diatomite composite photocatalytic material, comprising the following steps: The sol-gel method was used to prepare diatomite-loaded erbium-doped nano-TiO2 powder by doping erbium with purified diatomite as carrier and butyl titanate as titanium source. The diatomite-loaded erbium-doped nano-TiO2 powder is mixed with water, plant debris, a binder, a thickener and a dispersant to obtain an erbium-doped TiO2 / diatomite composite photocatalytic material; The preparation method of diatomite-loaded erbium-doped nano-TiO2 powder comprises: firstly adding butyl titanate and glacial acetic acid to a diatomite suspension, then dripping an erbium acetate solution, and controlling the Er content in the diatomite-loaded erbium-doped nano-TiO2 powder to increase. 3+ With Ti 4+ The molar ratio is 0.5~1:100.

[0026] In this embodiment, the method of first adding butyl titanate and glacial acetic acid to the diatomite suspension and then dripping the erbium acetate solution comprises: The purified diatomaceous earth and anhydrous ethanol solvent are fully stirred and mixed, and a diatomaceous earth suspension is prepared under ultrasonic treatment; butyl titanate and glacial acetic acid are sequentially added to the suspension and stirred and mixed to obtain a mixed solution; 0.1 g of erbium acetate is dissolved in 2 mL of deionized water, and then an appropriate amount of nitric acid is added to adjust the pH value to 3 to prepare an erbium acetate solution; the erbium acetate solution is added dropwise into the mixed solution and stirred to hydrolyze and condense butyl titanate in the mixed solution to produce titanium dioxide, thereby generating titanium dioxide colloid particles doped with erbium ions attached to the surface and pores of diatomite; after the hydrolysis and condensation reactions are completed, a sol is obtained; during the reaction, glacial acetic acid is added to inhibit hydrolysis; The method for preparing the diatomite-loaded erbium-doped nano-TiO2 powder also includes: Polyethylene glycol solution is added to the above sol, and the mixture is stirred to obtain a gel, which is aged, vacuum dried, ground and calcined to obtain diatomaceous earth-loaded erbium-doped nano-TiO2 powder.

[0027] Specific:

[0028] (1) Preparation of diatomite-loaded erbium-doped nano-TiO2 powder:

[0029] ① Use a 325 mesh screen to sieve the diatomite, take the diatomite under the sieve, and put the diatomite under the sieve into a 60wt% sulfuric acid aqueous solution for stirring and washing for 2~3h; then use 200~250W power ultrasonic treatment for 1~2h at 25~30℃, and then wash it with distilled water until it is neutral; then put it in a vacuum drying oven and dry it at 80℃ for 6h; finally put it in a muffle furnace and roast it at 550~600℃ for 3h to obtain purified diatomite, which is placed in a dryer for standby use. The purified diatomite with most of the surface impurities and mineral fragments removed reduces the interference of impurity ions on the formation process of the erbium ion-doped TiO2 crystal structure, and can be used as an ideal photocatalyst loading carrier.

[0030] ② 8g of purified diatomite and 90mL of anhydrous ethanol were added to the mixer in sequence, stirred for 30min, and ultrasonically treated at 400W power for 30min at 25°C to form a suspension, and stirring was continued. Then 18mL of butyl titanate and 9mL of glacial acetic acid were added in sequence, that is, glacial acetic acid was added after the addition of butyl titanate, and after the addition of butyl titanate and glacial acetic acid, stirring was continued to form a mixed solution. Among them, the mass ratio of the generated titanium dioxide to diatomite was 1:1.5~2; the volume ratio of butyl titanate to glacial acetic acid was 1:0.4~0.5.

[0031] ③ Add 0.1 g of erbium acetate and 2 mL of deionized water into the mixer in sequence, keep stirring, then add an appropriate amount of nitric acid, adjust the pH value to 3, and prepare an erbium acetate solution.

[0032] ④ Maintaining strong stirring, add the acetic acid bait solution into the mixed solution A at a rate of 1 drop every 3 to 5 seconds to form a sol.

[0033] ⑤ Add 0.2g polyethylene glycol (PEG2000) and 4mL deionized water into the mixer in sequence, treat with 200W ultrasonic wave at 25℃ to dissolve into a transparent solution, and add into the sol; keep stirring vigorously; wherein, the mass volume ratio of polyethylene glycol to sol is 0.3~0.4:100g / mL.

[0034] ⑥ Maintain strong stirring, the sol gradually forms a gel in a gel state, and then the gel is placed in a biochemical incubator and aged at 25°C for 24 hours.

[0035] ⑦ Take out the aged gel from the biochemical incubator, put it into a vacuum drying oven, dry it at 80°C and absolute pressure of 10 kPa for 8 hours, keep it warm for 16 to 24 hours, take it out, grind it into powder, and put it into a muffle furnace. The temperature is increased at a rate of 5°C / min and calcined at 500°C for 2 hours to obtain diatomaceous earth-loaded erbium-doped nano-TiO2 powder.

[0036] In the process of preparing diatomite-loaded erbium-doped nano-TiO2 powder, the stirring speed is preferably 800-2000 rpm. During the stirring process, the stirring speed increases with the increase of the viscosity of the material. In step ①, the stirring speed is preferably 800-1000 rpm; in steps ② and ③, the stirring speed is preferably 1000-1500 rpm; in steps ④, ⑤ and ⑥, the stirring speed is preferably 2000 rpm.

[0037] At the above stirring speed, the uniformity of erbium doping during the reaction process can be effectively improved, while keeping the material in a flowing state as a whole to avoid excessive solidification of some areas to form gel.

[0038] In the present invention, glacial acetic acid is added as a hydrolysis inhibitor, which can effectively inhibit the hydrolysis rate of butyl titanate and avoid the formation of precipitation during the dropwise addition of solution B. Polyethylene glycol is added as a pore former and stabilizer. After polyethylene glycol is roasted and decomposed in a muffle furnace, pores are generated on the titanium dioxide grain film layer, making it more firmly loaded in the pores of diatomaceous earth, and it is not easy to cause the film layer to break and fall off. As the molecular weight of polyethylene glycol increases, the skeleton strength of the titanium dioxide grain film layer increases and the capillary force decreases, and a film layer with a stable structure can be formed.

[0039] In the present invention, the sol-gel method is adopted to dope titanium dioxide with erbium ions and load diatomaceous earth, and the raw materials are uniformly mixed in the liquid phase, and hydrolysis and condensation chemical reactions are carried out to form a stable transparent sol system in the solution. After stirring and aging, the sol is slowly polymerized between the colloid particles, and the solvent in the three-dimensional network space structure loses fluidity to form a gel.

[0040] (2) Preparation of Er-doped TiO2 / diatomite composite photocatalytic materials:

[0041] An erbium-doped TiO2 / diatomite composite photocatalytic material comprises the following raw materials in parts by weight: 25-35 parts of water, 40-50 parts of diatomaceous earth loaded erbium doped nano-TiO2 powder, 5-10 parts of plant debris, 3-5 parts of binder, 2-5 parts of thickener, and 3-5 parts of dispersant.

[0042] The composite photocatalytic material is made into round particles for easy storage and use. The specific preparation method is as follows:

[0043] ① Plant debris is prepared by freeze-drying plant leaves at -80°C and 0.2MPa for 72 hours, grinding them into powder, and then passing them through a 325-mesh sieve to take the sieved material.

[0044] ② Mix water, diatomaceous earth loaded with erbium doped nano-TiO2 powder, plant debris, thickener, binder and dispersant according to a set ratio, stir evenly and make into round particles.

[0045] ③ Dry at 25°C for 24 to 36 hours to obtain erbium-doped TiO2 / diatomaceous earth composite photocatalytic material.

[0046] ④ The freeze-dried and ground plant leaf particles have a fresh smell, a rough surface, grooves, protrusions, soft hairs and other structures, and have a strong dust retention ability; they can not only adsorb and retain micron-sized particles, but also make the finished material produce a fresh smell. The binder is glutinous rice glue powder. The thickener is sodium carboxymethyl cellulose. The dispersant is a carboxylic acid copolymer salt, which can be acrylic acid-maleic acid copolymer sodium salt, butenedioic acid-styrene copolymer sodium salt or acrylic acid-maleic acid copolymer ammonium salt.

[0047] Example 1

[0048] First, the diatomaceous earth is purified.

[0049] The diatomite was screened with a 325 mesh screen, and the diatomite under the screen was placed in a 60wt% sulfuric acid solution for stirring and washing for 2 hours; it was treated with an ultrasonic wave with a power of 200W at 25°C for 1 hour, and it was repeatedly washed with distilled water until it was neutral; it was placed in a vacuum drying oven and dried at 80°C for 6 hours, and then placed in a muffle furnace and calcined at 550°C for 3 hours to obtain 1# purified diatomite, which was placed in a dryer for standby use. The 1# purified diatomite is high-purity micron-grade diatomite.

[0050] Then, diatomite-loaded erbium-doped nano-TiO2 powder was prepared according to the following steps.

[0051] (1) 8 g of purified diatomite and 90 mL of anhydrous ethanol were added to a beaker, sealed with a protective film, magnetically stirred for 30 min, and ultrasonically treated at 400 W for 30 min at 25 ° C; then, the magnetic stirring was replaced with mechanical stirring, and 18 mL of butyl titanate and 9 mL of glacial acetic acid were added during the mechanical stirring process, and a mixed solution was formed after mechanical stirring for 10 min. The stirring speed was controlled at 1000 rpm, wherein the mass ratio of the generated titanium dioxide to diatomite was 1:1.9, and the volume ratio of butyl titanate to glacial acetic acid was 1:0.5.

[0052] (2) Dissolve 0.1 g of erbium acetate (solid) in 2 mL of deionized water, add an appropriate amount of nitric acid, adjust the pH to 3, and form an erbium acetate solution. Then, use a dropping funnel to drip into the mixed solution at a rate of 1 drop every 3 to 5 seconds, and control the stirring speed of the mechanical stirrer at 1500 rpm to form a light yellow, transparent sol, in which Er 3+ With Ti 4+ The molar ratio is 0.55:100.

[0053] (3) Control the stirring speed at 1500 rpm, prepare a polyethylene glycol solution by mixing 0.2 g polyethylene glycol (PEG2000) with 4 mL deionized water, and add the solution to the sol. The mass volume ratio of polyethylene glycol to sol is 0.4:100 g / mL.

[0054] (4) The stirring speed was controlled at 2000 rpm, and the sol gradually formed a gel in a gel state, and then the gel was placed in a biochemical incubator and aged at 25°C for 24 hours.

[0055] (5) The aged gel was taken out from the biochemical incubator, placed in a vacuum drying oven, dried at 80°C and an absolute pressure of 10 kPa for 8 h, and kept warm for 16 h. The gel was taken out, ground into powder, and placed in a muffle furnace. The temperature was increased at a rate of 5°C / min and calcined at 500°C for 2 h to obtain diatomaceous earth-loaded erbium-doped nano-TiO2 powder, such as Figure 2 shown.

[0056] (6) Next, plant debris was prepared: the ginkgo leaves were freeze-dried at -80°C and 0.2 MPa for 72 h, ground and pulverized, and then passed through a 325-mesh sieve. The residue below the sieve was used as the raw material plant debris.

[0057] (7) Finally, 32 parts of deionized water, 50 parts of diatomaceous earth-loaded erbium-doped nano-TiO2 powder, 8 parts of plant debris, 5 parts of glutinous rice glue powder, 2 parts of sodium carboxymethyl cellulose, and 3 parts of sodium salt of acrylic acid-maleic acid copolymer were mixed and stirred evenly with a stirrer; the particles were made into particles of about 5 mm in size, and dried in a drying oven at a temperature of 30°C for 24 hours to prepare 1# erbium-doped TiO2 / diatomaceous earth composite photocatalytic material, which was then bagged for later use.

[0058] Comparative Example 1

[0059] Combined with the preparation method in "Preparation of Diatomaceous Earth-Loaded TiO2 Photocatalyst and Its Degradation Performance on Methyl Orange" of Xi'an University of Architecture and Technology.

[0060] First, the diatomaceous earth is purified.

[0061] The diatomite was screened with a 325 mesh screen, and the diatomite under the screen was placed in a 60wt% sulfuric acid solution for stirring and washing for 2 hours; it was treated with an ultrasonic wave with a power of 200W at 25°C for 1 hour, and it was repeatedly washed with distilled water until it was neutral; it was placed in a vacuum drying oven and dried at 80°C for 6 hours, and then placed in a muffle furnace and calcined at 550°C for 3 hours to obtain 1# purified diatomite, which was placed in a dryer for standby use. The 1# purified diatomite is high-purity micron-grade diatomite.

[0062] Then, diatomaceous earth-loaded nano-TiO2 powder was prepared according to the following steps.

[0063] (1) 8 g of purified diatomaceous earth and 90 mL of anhydrous ethanol were added to a beaker, sealed with a protective film, magnetically stirred for 30 minutes, and ultrasonically treated at 400 W for 30 minutes at 25°C; then, the magnetic stirring was replaced with mechanical stirring, and 18 mL of butyl titanate and 9 mL of glacial acetic acid were added during the mechanical stirring process. After mechanical stirring for 10 minutes, a mixed solution was formed. The stirring speed was controlled at 1000 rpm.

[0064] (2) Add an appropriate amount of nitric acid to 4 mL of deionized water and adjust the pH value to 3 to form a solution. Then, use a dropping funnel to drip into the mixed solution at a rate of 1 drop every 3 to 5 seconds. Control the stirring speed of the mechanical stirrer at 1500 rpm to form a light yellow, transparent sol.

[0065] (3) Control the stirring speed at 1500 rpm, prepare a polyethylene glycol solution by mixing 0.2 g polyethylene glycol (PEG2000) with 4 mL deionized water, and add the solution to the sol. The mass volume ratio of polyethylene glycol to sol is 0.4:100 g / mL.

[0066] (4) The stirring speed was controlled at 2000 rpm, and the sol gradually formed a gel in a gel state, and then the gel was placed in a biochemical incubator and aged at 25°C for 24 hours.

[0067] (5) The aged gel was taken out from the biochemical incubator, placed in a vacuum drying oven, dried at 80°C and an absolute pressure of 10 kPa for 8 h, and kept warm for 16 h. The gel was taken out, ground into powder, and placed in a muffle furnace. The temperature was increased at a rate of 5°C / min and calcined at 500°C for 2 h to obtain diatomaceous earth-loaded nano-TiO2 powder.

[0068] (6) Next, plant debris was prepared. The ginkgo leaves were freeze-dried at -80°C and 0.2 MPa for 72 h, ground and pulverized, and then passed through a 325-mesh sieve. The residue below the sieve was used as the raw material plant debris.

[0069] (7) Finally, deionized water, diatomaceous earth-loaded nano-titanium dioxide, plant debris, sodium carboxymethyl cellulose, glutinous rice glue powder, and sodium salt of acrylic acid-maleic acid copolymer are mixed and stirred evenly with a stirrer; particles of about 5 mm are made and placed in a drying oven at a temperature of 30°C for 24 hours to prepare a TiO2 / diatomaceous earth composite photocatalytic material, which is then bagged for later use.

[0070] The Example 1 and the Comparative Example 1 were tested and the results were obtained. Figure 3 The specific detection process is as follows:

[0071] The sample is placed in a cylindrical volume of approximately 2m 3 The sealed box contains 8 layers of square pallets, each with an area of ​​0.09m 2 Each tray contains 2g of sample (16g in total), and a circulating fan is installed in the sealed box. During the test, the temperature in the box is 25℃, the humidity is 50-60%, the light intensity is 4200Lux, and the fan in the box operates normally.

[0072] Each time, 2 μL of formaldehyde was injected into the sealed box, forming an initial concentration C0 of about 1.0830 mg / m 3 An air sampler was used to collect equal amounts of gas from the closed box at 15 min, 30 min, 60 min, 90 min, 120 min, 150 min and 180 min, and a gas chromatograph was used to determine the formaldehyde content in the gas samples, which was converted into volume concentration. The ratio of the concentration difference to the sample concentration in the blank container was the formaldehyde degradation and removal rate.

[0073] from Figure 3 The degradation of formaldehyde can be seen in the figure. After 180 minutes, the formaldehyde concentration C in Example 1 and Comparative Example 1 is t 0.0225 mg / m 3 and 0.1532mg / m 3 , the degradation and removal rates were 97.92% and 85.85% respectively, indicating that the material can expand the spectral corresponding range of TiO2 to the visible light region and improve the material's treatment effect on harmful gaseous pollutants.

Claims

1. A method for preparing an erbium-doped TiO2 / diatomite composite photocatalytic material, characterized in that: The following steps are involved: The sol-gel method was used to prepare diatomite-loaded erbium-doped nano-TiO2 powder by doping erbium with purified diatomite as carrier and butyl titanate as titanium source. The diatomite-loaded erbium-doped nano-TiO2 powder is mixed with water, plant debris, a binder, a thickener and a dispersant to obtain an erbium-doped TiO2 / diatomite composite photocatalytic material; The preparation method of diatomite-loaded erbium-doped nano-TiO2 powder comprises: firstly adding butyl titanate and glacial acetic acid to a diatomite suspension, then dripping an erbium acetate solution, and controlling the Er content in the diatomite-loaded erbium-doped nano-TiO2 powder to increase. 3+ With Ti 4+ The molar ratio is 0.5~1:

100.

2. The method for preparing the erbium-doped TiO2 / diatomite composite photocatalytic material according to claim 1, characterized in that: The method of first adding butyl titanate and glacial acetic acid to a diatomite suspension and then dripping an erbium acetate solution comprises: The purified diatomaceous earth and anhydrous ethanol solvent are fully stirred and mixed, and a diatomaceous earth suspension is prepared under ultrasonic treatment; butyl titanate and glacial acetic acid are sequentially added to the suspension and stirred and mixed to obtain a mixed solution; 0.1 g of erbium acetate is dissolved in 2 mL of deionized water, and then an appropriate amount of nitric acid is added to adjust the pH value to 3 to prepare an erbium acetate solution; the erbium acetate solution is added dropwise into the mixed solution and stirred to hydrolyze and condense butyl titanate in the mixed solution to produce titanium dioxide, thereby generating titanium dioxide colloid particles doped with erbium ions attached to the surface and pores of diatomite; after the hydrolysis and condensation reactions are completed, a sol is obtained; during the reaction, glacial acetic acid is added to inhibit hydrolysis; The method for preparing the diatomite-loaded erbium-doped nano-TiO2 powder also includes: Polyethylene glycol solution is added to the above sol, and the mixture is stirred to obtain a gel, which is aged, vacuum dried, ground and calcined to obtain diatomaceous earth-loaded erbium-doped nano-TiO2 powder.

3. The method for preparing the erbium-doped TiO2 / diatomite composite photocatalytic material according to claim 2, characterized in that: The mass ratio of the produced titanium dioxide to diatomaceous earth is 1:1.5~2, and the volume ratio of butyl titanate to glacial acetic acid is 1:0.4~0.

5.

4. The method for preparing the erbium-doped TiO2 / diatomite composite photocatalytic material according to claim 2, characterized in that: The erbium acetate solution is added dropwise to the mixed solution at a rate of 1 drop every 3 to 5 seconds.

5. The method for preparing the erbium-doped TiO2 / diatomite composite photocatalytic material according to claim 2, characterized in that: The mass volume ratio of polyethylene glycol to sol is 0.3~0.4:100g / mL.

6. The method for preparing the erbium-doped TiO2 / diatomite composite photocatalytic material according to claim 2, characterized in that: The aging conditions are to react at 25°C for 24 hours, the vacuum drying conditions are to dry at 80°C and an absolute pressure of 10 kPa for 8 hours and keep warm for 16 to 24 hours, and the calcination conditions are to heat to 500°C in a muffle furnace at a heating rate of 5°C / min and calcine at this temperature for 2 hours.

7. The method for preparing the erbium-doped TiO2 / diatomite composite photocatalytic material according to claim 2, characterized in that: When the mixture of diatomaceous earth and anhydrous ethanol is stirred, the stirring speed is 800-1000 rpm, and when the sol and gel are obtained by stirring, the stirring speed is 2000 rpm.

8. The method for preparing the erbium-doped TiO2 / diatomite composite photocatalytic material according to claim 1, characterized in that: The diatomite-loaded erbium-doped nano-TiO2 powder is mixed with water, plant debris, a binder, a thickener and a dispersant, and the proportions of each substance are calculated according to the following weight parts: 25~35 parts water, 40~50 parts of diatomite-loaded erbium-doped nano-TiO2 powder, 5~10 portions of plant debris, 3~5 parts of adhesive, Thickener 2~5 parts, 3~5 parts of dispersant.

9. The method for preparing the erbium-doped TiO2 / diatomite composite photocatalytic material according to claim 8, characterized in that: The binder is glutinous rice glue powder, the thickener is sodium carboxymethyl cellulose, the dispersant is carboxylic acid copolymer salts, and the plant debris is prepared by freeze-drying plant leaves at -80°C and 0.2MPa for 72 hours, grinding and crushing, and then passing through a 300-325 mesh sieve.

10. The method for preparing the doped TiO2 / diatomite composite photocatalytic material according to claim 2, characterized in that: The steps for purifying diatomaceous earth are: The diatomaceous earth is sieved with a 325-mesh sieve, and the diatomaceous earth under the sieve is taken out and placed in a 60wt% sulfuric acid aqueous solution for stirring and washing for 2-3 hours; then, it is treated with an ultrasonic wave with a power of 200-250W for 1-2 hours at 25-30°C, and then washed with distilled water until it is neutral; then, it is placed in a vacuum drying oven and dried at 80°C for 6 hours; finally, it is placed in a muffle furnace and calcined at 550-600°C for 3 hours to obtain purified diatomaceous earth, which is placed in a dryer for standby use.